(untitled) (مجلة إحالات, 2026)
The current researcher work aims at scrutinizing the effectiveness of computer-mediated peer feedback on EFL learners’ written performance. The study targets second-year students at the Department of English at M’sila University. The data were gathered through a questionnaire administered to 30 students from the same department. The obtained results revealed that computer-mediated peer feedback is not implemented among second-year EFL students at the University of M’sila to enhance their writing quality and that students still rely on teachers’ feedback in face-to-face settings. Henceforth, implementing technology-enhanced peer response as a technique to enhance EFL students’ written performance is required.